Diagnostics of accomplishing regional goals of the national project “Ecology” (on the example of the Vologda region) - E. N. Yakovleva; M. V. Andreeva; I. V. Krukova (Вестник университета, 2024)
The article provides a comparative analysis of the structure of funding sources for the national project “Ecology”. A comprehensive assessment of the interim results of implementing regional projects in the Vologda region was conducted as part of the national project in question using the method of earned value. As a result, a discrepancy was revealed in the structure of financial support for the implementation of the national project on a federal and regional scale both in sources and in items of expenditure, which is explained by the specifics of the goals and powers of different levels of management. In the Vologda region, low involvement of local governments and the private sector in the development of the national project “Ecology” was found. Underestimation of the target values of the results of project activities is indicated as a significant reason for the proven high efficiency of applying financial resources in the implementation of regional projects. To improve strategic environmental management, it was proposed to use stimulating measures for increasing the number of stakeholders and the amount of funding, to use a scenario approach. In general, the identified problems are typical for many constituent entities of the Russian Federation, therefore, the authors’ recommendations for their solution can be widely applied and will increase the efficiency of environmental activities and the quality of performance of the national project “Ecology”.